Etická dimenze profese pedagoga volného času - Michal Kaplánek (Karolinum Press, 2019)
The paper defines the importance and the resources of professional ethics in education. The general principles are applied to leisure educators, as they are understood and embedded in the Czech legislation. The attempts to establish professional conduct outlines also for leisure educators led to establishing codes of ethics in several leisure-time and out-of-school centers. The aim of the present study is to point out the specific features of the ethical dimension for this profession, and to attempt to answer the question whether the current codes of ethics of the mentioned centers can be considered suitable tools for enhancing the ethical competence of leisure educators they employ. Based on the analysis of both the content and the origin of these codes of ethics, the author concludes that the mere creation of these documents is not sufficient in increasing the sensibility of leisure educators towards the ethical issues within their profession.